The Relationship Between Sexual Aggression Victimization and Perpetration and Other Types of IPV Among Iranian Married Individuals. Issue 13 (July 2021) - Nikparvar, Fatemeh; Stith, Sandra; Spencer, Chelsea; Panaghi, Laily
This study examined the relationship between sexual intimate partner violence (IPV) victimization and perpetration and other types of IPV among married men and women in Tehran, Iran. Data were collected from 116 males and 121 females who reported perpetrating or experiencing IPV at least once in the past year. Four path analyses were conducted to examine the relationships between different types of violence and sexual aggression. The model explained 57% of the variance in men's sexual aggression perpetration and 44% of the variance in women's sexual aggression perpetration. Also, the model explained 58% of the variance in men's and 45% of the variance in women's sexual aggression victimization. Findings of this study emphasize the importance of understanding how one type of violence can be a context for other types of violence.